The Case of Jahi McMath - Keisha Ray (Voices in Bioethics, 2014)
I have been following the very unfortunate case of Jahi McMath. McMath is a 13-year-old African-American child in California. She went into cardiac arrest and suffered irreparable brain damage after undergoing a tonsillectomy to relieve sleep apnea.5 Her story has frequently been in the news and has been portrayed as a battle between Children’s Hospital Oakland, where her surgery was held, and her parents, who disagreed with the hospital’s recommendation to discontinue all life-sustaining practices. This battle has both legal and medical components. Medical practitioners, children’s rights advocates, right-to-life groups, legal experts, and bioethicists have all weighed in on the relevant issues that a case like Jahi McMath raises.